Austerity's Model Pupil: The Ideological Uses of Ireland during the Eurozone Crisis. (July 2019) - Coulter, Colin; Arqueros-Fernández, Francisco; Nagle, Angela
During the Eurozone crisis, Ireland would come to be regarded widely as a 'poster child' for the remedial powers of the austerity agenda and as a 'role model' for the other heavily indebted states. In this article, we offer a critical reading of the narrative of an Irish 'recovery' that has gained currency over recent years. Tracing the genealogy of terms such as 'poster child' and 'role model' reveals that they predate the recent apparent revival in Ireland's economic fortunes. The specific point of origin of these metaphors suggests that the often euphoric discourse that has come to attend the Irish economy articulates a very specific political enterprise. In their efforts to cast the country as the harbinger of economic 'recovery', powerful political players have sought to make ideological use of Ireland to ensure that repayments would continue to flow from those European countries in which private bank debts were socialized after the crash. The success of this endeavour has meant that the crisis in the Eurozone has been resolved in the interests of those powerful forces that sparked it in the first place.